On the Changes in the Thermal Structure of the Atmosphere over Agra associated with passage of Western Disturbance in Winter. - ANANTHAKRISHNAN, R. (MAUSAM, 1950)
The large flucations in the thermal structure of the upper troposphere and lower stratosphere over Agra in association with the passage of western disturbance is presented. Large variations of temperature occurred above 8 g kms with comparatively little variation below. In association with passage of western disturbance, horizontal air movements extending to very great altitudes are observed. Short period changes in the thermal structure are attributed to the passage of tropopause wave over the station.